Sosialisasi Inovasi APE (Alat Permainan Edukatif) bagi Guru RA se-Kecamatan Plered dan Tegalwaru pada Masa Pandemi Covid-19 - purwani, annisa
Early childhood education in the golden age is very important because at this time children's intelligence is growing rapidly. The stimulation given is not only for cognitive intelligence but also for social emotional, character, and noble character needs to be stimulated. The role of teachers and parents in facilitating children when providing learning stimuli through their experiences needs to be designed and arranged in such a way that all aspects of children's development can develop optimally, therefore there is a need for educational game tools as learning facilities for early childhood. APE innovation socialization was carried out to RA teachers in Plered and Tegalwaru sub-districts in two stages, namely presentation and training, the first stage was in the form of exposure to the importance of APE in the learning process in early childhood, the second stage was training involving participants in carrying out APE innovation-making activities in developing all aspects early childhood development. Based on the results of the analysis of the interview and observation data, it was revealed that the creativity of teachers in making APE innovations could increase not only by providing material but also participants being directly involved in the manufacturing process and sharing innovations with colleagues so that innovation could develop.